2005
DOI: 10.1128/jvi.79.17.11443-11456.2005
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Leukemia Virus Common Integration at the Kis2 Locus: Simultaneous Overexpression of a Novel Noncoding RNA and of the Proximal Phf6 Gene

Abstract: Retroviral tagging has been used extensively and successfully to identify genes implicated in cancer pathways. In order to find oncogenes implicated in T-cell leukemia, we used the highly leukemogenic radiation leukemia retrovirus VL3 (RadLV/VL3). We applied the inverted PCR technique to isolate and analyze sequences flanking proviral integrations in RadLV/VL3-induced T lymphomas. We found retroviral integrations in c-myc and Pim1 as already reported but we also identified for the first time Notch1 as a RadLV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 72 publications
4
21
0
Order By: Relevance
“…However, this is only speculation, which needs further experimental substantiation. 1 More recently, Landais et al 6 reported the existence of six other isoforms of the Phf6 gene in mouse. Their function is not clear although five of them (t1, t4, t5, t6 and t7) can potentially give rise to alternative Phf6 protein isoforms.…”
Section: Genementioning
confidence: 99%
See 4 more Smart Citations
“…However, this is only speculation, which needs further experimental substantiation. 1 More recently, Landais et al 6 reported the existence of six other isoforms of the Phf6 gene in mouse. Their function is not clear although five of them (t1, t4, t5, t6 and t7) can potentially give rise to alternative Phf6 protein isoforms.…”
Section: Genementioning
confidence: 99%
“…More recently, mouse Phf6 protein was found overexpressed in tumors with rearrangements (radiation leukemia virus, RadLV integration) in the neighboring Kis2 locus (noncoding RNA; Unigene cluster Mm.277876, B250 kb proximal to the Phf6 gene). 6 Overall there is very little information on the function of the PHF6 protein available. If we dare to speculate, based on the X-inactivation skewing in carrier females, 1,2 localization of the PHF6 protein to the cell nucleus and nucleolus 1,6,8 and the latest observations of the Phf6 protein overexpression in specific mouse tumors, 6 we would suggest an important role for PHF6 in cell growth and proliferation, which may be achieved via its participation in ribosome biogenesis (at the RNA and/or protein level).…”
Section: Function Of the Proteinmentioning
confidence: 99%
See 3 more Smart Citations